An in vitro production and field transfer protocol for Solanum melongena L. plants - Taha, R.M.; Tijan, M. (2003)
In vitro plantlet regeneration studies were initiated from various vegetative organs of Solanum melongena L. Best shoot regeneration (25 shoots per explant) was obtained from leaf and stem explants (17 shoots per explant) cultured on MS medium supplemented with 0.5mg/I Naphthalene acetic acid (NAA), although multiple shoots were observed routinely on MS basal and MS containing 1.0-6.0mg/l NAA on both leaf and stem explants. Rooting of shoots (approximately 100) was achieved on MS basal medium. Regenerated plantlets were then acclimatised by transferring them to enclosed glass containers (18cm x 118cm x 25cm) which had the lids opened 5-10 minutes each day for 14 days. The plantlets were then transferred to fields with no shades with 80 success; plants that survived produced fruits. Karyotype analysis coupled with measurement of the mitotic index revealed neither somaclonal variation nor impaired frequency of cell division.